Upaya Meningkatkan Hasil Belajar Siswa Kelas III SDN Uteran 01 melalui Penerapan Experiental Learning pada Mata Pelajaran IPA Materi Hewan di Sekitar Kita - Al Ainy Imana Anshari; Vivi Rulviana; Aning Triastuti (PT PUSTAKA CENDEKIA GROUP, 2025)
The low learning outcomes of students in science subjects, particularly in the material about animals around us, is one of the main issues in primary education. Previous research has shown that students' science learning outcomes often demonstrate unsatisfactory achievement. Survey data from various sources indicate that the percentage of students who meet the learning objectives for this material is below the standards set in the national curriculum. The purpose of this study is to identify efforts to improve the learning outcomes of third-grade students at SDN Uteran 01 through the implementation of Experiential Learning in the Science subject, focusing on the material of animals around us. The method used in this research is the Classroom Action Research method, involving 15 students. The data collection method employed is testing. The results of the study indicate that the Experiential Learning method has a positive impact on improving the learning outcomes of third-grade students at SDN 01 Uteran in the Science subject related to animals around us.